Strategic Management Model Validation with Descriptive Statistical Modeling and Hypothesis Testing: The Impact of Manager Support on Employee Attitudes and Organizational Performance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This particular research suggested as well as examined the trickle-down model which manager support from the functional department level affect entrance collection employees’ attitudes towards boss support from the operational level as well as consequently impact leader-member trade, organizational citizenship behavior, as well as turnover motives. Many years associated with research obviously display which relying upon traditional organizational power bases isn’t efficient whenever businesses wish to market company ethics as well as overall performance. It’s not just which the utilization of genuine power to determine ethics codes as well as coercive power in order to discipline employees that don’t conform doesn’t work This particular paper is based on the multi-method, statistical research approach within the retail industry, signifies which the traditional metal closed fist leads in order to unethical company values as well as lower service overall performance.